ANALYSIS OF INTERNAL EXTERNAL FACTORS IN BUSINESS DEVELOPMENT STRATEGY AT CV. FERYAL MEDIKA - Wahida Nur Fitriani; Abd. Rahman Kadir (Scientia Integritas Utama, 2023)
The research aims to determine both internal and external environmental factors that affect the company's business by CV. Medicaid in its corporate growth. This study uses qualitative research. Triangulation of three methods—direct observation, semi-structured interviews, and documents—is the method used to collect data. Primary data and secondary data are two types of data sources. EFE Matrix (External Factor Evaluation), IFE Matrix (Internal Factor Assessment), and SWOT Analysis Matrix on CV. Feryal Medika was used to process data descriptively. This study shows that CV. Feryal Medika is influenced by four strengths, four weaknesses, two opportunities and three threats.